Spatial construction in Shanghai lady: a Chinese adaptation - Liang, Chen (Nordlit, 2015)
This article aims to provide spatial analysis of an adaptation of Ibsen’s The Lady from the Sea and the musical Shanghai Lady staged in China in 2009 and directed by Shi Jun, a young Chinese associate professor from Shanghai Theatre Academy. The notion of space may be viewed from two perspectives: first, as a textual construction, it reflects the characterization applied and theme shaped by the director; second, as an on-stage theatrical technique, it conveys the director’s understanding and innovative manoeuvre of adaptation in the target culture. The article tries to analyse the spatial renovation in Shanghai Lady, both in the text and on the stage, from the two perspectives mentioned above and aims to reveal the contemporary Chinese ideological reception of Ibsen’s plays and the literary techniques exhibited in its adaptation.